Real-Time Simulator of a Six Degree-of-Freedom Hydraulic Manipulator for Pipe-Cutting Applications - Myoungho Kim (IEEE, 2021)
Hydraulic manipulators exhibit significant potential for various applications owing to their advantages. To simulate scenarios and evaluate their control performance effectively, a real-time simulation method of hydraulic manipulators is required. Simulations are easier and safer to conduct, and are therefore preferred over physical experiments. This paper discusses a real-time simulator for hydraulic manipulators. This simulator entails servo valve dynamics, hydraulic equations, a friction model, a pipe-cutting model, mechanical manipulator dynamics, a robust numerical integration algorithm, and a controller. The hydraulic manipulator dynamics was developed by considering the compressibility of fluid and applying the multibody recursive formula to effectively implement the characteristics of the actual system. In addition, a noniterative HHT- $α $ numerical integration algorithm was applied to real-time simulations including the stiff characteristics of the hydraulic system and the cutting force. The performance of the real-time simulator was verified by comparing the results obtained with the results of the open-loop control experiment. The results of circular trajectory-tracking and pipe-cutting simulations showed that an advanced simulation with a controller can be realized in a working environment, and the real-time performance was verified by measuring the computational time.